Comparative analysis of the journal General Medicine and regional scientific publications: Bibliometric indicators, publication trends, and impact factors (1995–2024) - Miljković, Ana; Kostić, Milena; Stanković, Suzana; Lapčević, Mirjana; Punoševac, Darinka; Trifunović Balanović, Dragana; Vojnović, Matilda (General Practice, 2025)
Introduction. The Journal General Practice (JGP), founded in 1995 as the official journal of Section of General Practice of Serbian Medical Society, is dedicated to topics from primary health care (PHC), clinical practice and preventive medicine.Objective. The aim of this article was to, after analyzing the structure and thematic areas of the JGP, make a comparison with leading academic journals in the field of general/family medicine in Western and Eastern Europe and Balkans.Method. Comparative bibliometrics was applied comparing bibliometric indicators, publicational trends and influencing factors of the JGP with the British Journal of General Practice (BJGP), Family Medicine & Primary Care Review and Croatian Medical Journal (CMJ).Results. In the structure of articles in JGP dominates original scientific articles (30%), review papers (25%), case reports (15%), while educational articles, announcements, polemics and historical articles participate with 10% each. Major subject areas include PHC, clinical medicine, epidemiology, preventive medicine and health policy. Most of the authors are from Serbia with a small participation of foreign authors (1.5%). The journal does not have an official Journal Citation Report (JCR) impact factor, while compared journals have JCR factors 5.3 (BJGP), 0.5 (Family Medicine & PCR) and 1.3 (CMJ). The average number of published articles is 15–20, which is lower in comparison with the aforementioned journales.Conclusion. The Journal General Practice showed a continuated development, following modern challenges in medicine, especially in PHC. Its diversity of content and educational character make it an important resource for experts in the health system.
Keywords: journal; general medicine; primary healthcare